Benign Tumor in Labia Minora - Putra, Hadrians Kesuma; Anggraeni, Asih; rinaldi, andi; moegni, fernandi (Sriwijaya Journal of Medicine, 2018)
Vulva tumors are generally a rare disease encountered in gynecological clinical practice, especially at a young age. Vulvar tumors, more common in the labia major and rarely in the labia minor, clitoris, vestibulum, and posterior comicura. The most common vulvar benign tumors are fibroma, papilloma, lipoma, angioma, and others. A 39-year-old woman, at RSCM Urogynecology Jakarta clinic with chief complain mass or swelling in right labia minor. Size of mass increases in period of one year. Mass began to grow at 8 months of pregnancy. By 2014, patients have same mass in the right and left labia minor, and tumor excision has been performed. Conclusions of the specimens sent for pathological assessment are fibroepithelial papillomas. Gynecological and palpation examinations show 2 solid papilloma masses, in right labia minor, 8x4x2 cm and 3x2x2cm, painless, and firmly defined. In mons pubis area, skin looks coarse, thickened, hyperkeratotic. Speculum examination showed no abnormality. Patient diagnosed as a recurrent minor armored labia tumor. On December 5, 2017 an excision and reconstruction operation was conducted. Obtained pathological exam on December 20, 2017 with results stromal fibroepithelial polyps. Among all tumors in the vulva, tumors in labia minor appear less frequently. Biopsy should be performed for histologic examination to exclude malignant allegations. Furthermore, because of the location and size of the tumor, it can cause severe interference symptoms in the patient and therefore early diagnosis and treatment is essential.